1、f(-1) = 2^1 = 2;f(0) = 2^0 = 1;f(1) = f(1-1) - f(1-2) = f(0) - f(-1) = 1 - 2 = -1 = -f(0);f(2) = f(1) - f(0) = -f(0) - f(0) = -2f(0);f(3) = f(2) - f(1) = -2f(0) + f(0) = -f(0);f(4) = f(3) - f(2) = -f(0) + 2f(0) = f(0);f(5) = f(4) - f(3) = f(0) + f(0) = 2f(0);f(6) = f(5) - f(4) = 2f(0) - f(0) = f(0);f(7) = f(6) - f(5) = f(0) - 2f(0) = -f(0);f(8) = f(7) - f(6) = -f(0) - f(0) = -2f(0);可见,f(6) = f(0),f(7) = f(1),……,f(x)是周期为6的周期函数。2020/6 = 336……4,所以f(2020) = f(3) = -f(0) = -1 。2、f(1) = f(-2);f(2) = f(-1),……,f(x)是周期为3的周期函数。f(5) = f(2) = f(-1) = (-1)^2 - 2^(-1) = 1 - 1/2 = 1/2 。